Grid integration of PV systems - Zin, Lin Swe (2014)
In the project, simulation study is conducted on conventional grid integrated PV system. The system is divided into two sections, PV module with DC-DC converter and grid-connected DC-AC inverter which is assumed to be connected to a fixed DC bus. PV module is modelled as single diode representation. Maximum Power Point Tracking using Incremental Conductance is integrated to DC-DC converter. Inverter for the system uses full bridge topology with Sinusoidal Pulse-Width Modulation (SPWM) technique. Inverter grid current control using Proportional Resonance controller and grid synchronization using state-space approach is modelled and analyzed. A different approach of grid tied inverter using series resonant topology and phase shift modulation is developed as Simulink model and experimented on hardware prototype.